Mediating factors on the association between fear of falling and health-related quality of life in community-dwelling German older people: a cross-sectional study - Gottschalk, Sophie; König, Hans-Helmut; Schwenk, Michael; Jansen, Carl-Philipp; Nerz, Corinna; Becker, Clemens; Klenk, Jochen; Dams, Judith (BMC geriatrics, 2020)
Previous research has shown that not only falls, but also fear of falling (FoF) influences health-related quality of life (HrQoL) negatively. The EQ-5D (consisting of an index and a visual analogue scale [EQ-VAS]) is a frequently used instrument to determine HrQoL in clinical studies and economic evaluations, but no previous study compared the association between FoF and the EQ-5D index with the association between FoF and the EQ-VAS. Moreover, factors that influence the association between FoF and HrQoL are rarely examined. Thus, this study aimed to examine the association between FoF and HrQoL and to examine factors that mediate the association.
Gesehen am 30.11.2020